Oocyte Spontaneous Activation: An Overlooked Cellular Event That Impairs Female Fertility in Mammals - Cui, Wei (Frontiers in Cell and Developmental Biology, 2021)
In mammals, including humans, mature oocytes are ovulated into oviduct for fertilization. Normally, these oocytes are arrested at metaphase of the second meiosis (MII) and this arrest can be maintained for a certain period, which is essential for fertilization in vivo, and oocyte manipulations in vitro, such as assisted reproduction in clinics and nuclear/spindle transfer in laboratories. However, in some species and under certain circumstances, exit from MII occurs spontaneously without any obvious stimulation or morphological signs, which is so-called Oocyte Spontaneous Activation (OSA). This mini-review summarizes two types of OSA. In the first type (e.g., most rat strains), oocytes can maintain MII arrest in vivo, but once removed out, oocytes undergo OSA with sister chromatids separated and eventually scattered in cytoplasm. Because the stimulation is minimal (oocyte collection itself), this OSA is incomplete and cannot force oocytes into interphase. Notably, once re-activated by sperm or chemicals, those scattered chromatids will form multiple pronuclei (MPN), which may recapitulate certain MPN and aneuploidy cases observed in fertility clinics. The second type of OSA occurs in ovarian oocytes (e.g., certain mouse strains and dromedary camel). Without ovulation or fertilization, these OSA-oocytes can initiate intrafollicular development but these parthenotes cannot develop to term due to aberrant genomic imprinting. Instead, they either degrade or give rise to ovarian teratomas, which have also been reported in female patients. Last but not least, genetic models displaying OSA phenotypes and the lessons we can learn from animal OSA for human reproduction are also discussed.